Plasma-activated water treatment delayed the lipid oxidation and degradation of golden pompano fillets during storage based on lipidomics - Boyan Zhao; Yuxuan Gong; Jun Cao; Longteng Zhang; Bin Zhang; Fawen Yin; Hesham El-Seedi; Hui Ye; Jun Yang; Zhongyuan Liu; Jiamei Wang; Mingmin Chen; et al. (Food Chemistry: X, 2025)
Lipid oxidation and degradation during storage represent key challenges affecting the quality of golden pompano (Trachinotus blochii) fillets. This study aimed to investigate the dynamic changes in lipid profiles of plasma-activated water (PAW)-treated fillets over 18 days, using chemical analysis and UHPLC-MS-based lipidomics. The results showed that the PAW-treated group exhibited higher POV and TBARS values within 0–6 days, but significantly delayed their increase within 6–18 days. Lipidomics analysis identified 1985 lipids, classified into 5 major classes and 42 subclasses. PAW treatment generated 139 DALs, primarily enriched in the glycerophospholipid metabolic pathway. Furthermore, PAW treatment preserved the levels of TG, PC, PE, and CL while reducing the accumulation of LPC, LPE, MLCL, and FAs. Notably, the PAW-treated group maintained a higher level of PUFAs at 28.97 %. These findings demonstrate PAW as an effective strategy for mitigating lipid oxidation and degradation, with substantial potential for extending the shelf life of fillets.